Tourism, magic and modernity : cultivating the human garden - Picard, David (New York : Berghahn Books, 2011)
'Drawing from extended fieldwork in La R{u2975}nion, in the Indian Ocean, the author suggests an innovative re-reading of different concepts of magic that emerge in the global cultural economics of tourism. Following the making and unmaking of the tropical island tourism destination of La R{u2975}nion, he demonstrates how destinations are transformed into magical pleasure gardens in which human life is cultivated for tourist consumption. Like a gardener would cultivate flowers, local development policy, nature conservation, and museum initiatives dramatise local social life so as to evoke modernist paradigms of time, beauty and nature. Islanders who live in this'human garden' are thus placed in the ambivalent role of'human flowers', embodying ideas of authenticity and biblical innocence, but also of history and social life in perpetual creolisation.'--P. [4] of cover.
Introduction. Penguins in the Paris underground -- Tourism and magic -- Creole beautiful -- Cultivating society as a human garden -- Hospitality and love -- Bougainvilleas at the riverside -- Poachers in the coral garden -- History as an aesthetics of everyday life -- Towards a global gardening state.
Includes bibliographical references (p. 171-186) and index.
Keywords: Tourism -- Social aspects; Culture and tourism; Magic -- Social aspects; Anthropology -- Social aspects